PENGARUH KOMPETENSI, LINGKUNGAN KERJA DAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI SUPERVISOR TERHADAP KINERJA GURU DI SMA NEGERI 1 BATANG CENAKU - Darmanto Darmanto; Woro Utari; Indra Prasetyo (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to find and describe the conditions of competence, work environment, leadership of the principal as a supervisor and teacher performance in SMA Negeri 1 Batang Cenaku. In addition to knowing and analyzing, the work environment and leadership of the principal as a simultaneous and significant partial to the performance of teachers in SMA Negeri 1 Batang Cenaku. The population in this study is all teachers in SMA Negeri 1 Batang Cenaku who directed 32 people. With sampling technique using sampling census, where all members of the company serve as a sample. Results of simultaneous data analysis of teachers, environment and leadership that have a significant influence on the performance of teachers SMA Negeri 1 Batang Cenaku. And partially the working environment and leadership of principals have a significant influence on the performance of teachers SMA Negeri 1 Batang Cenaku. While the variable of teacher competence, partially does not have a significant influence on the performance of teachers SMA Negeri 1 Batang Cenaku Keywords: competence, work environment, leadership, performance